Observation of the Effect of Singulair Combined With Ketotifen in the Treatment of Acute Exacerbation of Chronic Obstructive Pulmonary Disease With Airway Hyperresponsiveness and Its Influence on Th17/Treg - Wang, Haiou; Qu, Gaojie (Frontiers in Surgery, 2022)
Objective: To investigate the effect of montelukast sodium (singulair) combined with ketotifen fumarate on the acute exacerbation of chronic obstructive pulmonary disease (AECOPD) with airway hyperresponsiveness (AHR) and its effect on Th17/ Treg. Methods: 168 patients with AECOPD and AHR diagnosed in our hospital from February 2018 to December 2019 were selected, and divided into the observation group (n=84) and the control group (n=84). Both groups were given anti infection, bronchodilator, glucocorticoid, phosphodiesterase inhibitor, cough and expectorant. The observation group was additionally treated with singulair tablets and ketotifen tablets for 14 days. The curative effect were observed after treatment. The first second forced expiratory volume (FEV1), forced vital capacity (FVC) and FEV1 as percentage of predicted value (FEV1% pred), blood oxygen pressure (PaO2) and blood carbon dioxide pressure (PaCO2), high-sensitivity C-reactive protein (hs-CRP) and procalcitonin (PCT), Th17 and Treg levels were measured in both groups before and after treatment. Results: Compared with the control group, the total effective rate after treatment in the observation group was increased (94.05% vs 75.00%, P<0.05). Compared with before treatment, the FEV1, FVC and FEV1%pred levels of the two groups of patients after treatment were increased (P<0.05). Compared with the control group, the FEV1, FVC and FEV1%pred levels of the observation group were increased after treatment (P<0.05). Compared with before treatment, the PaCO2, hs-CRP and PCT levels of the two groups of patients were reduced after treatment, and PaO2 levels were increased (P<0.05). Compared with the control group, the PaCO2, hs-CRP and PCT levels in the observation group were reduced after treatment, and the PaO2 level was increased (P<0.05). Compared with before treatment, Th17 and Th17/Treg levels of the two groups of patients were reduced after treatment, and Treg levels were increased (P<0.05). Compared with the control group, the Th17 and Th17/Treg levels of the observation group were reduced after treatment, and the Treg levels was increased (P<0.05). Conclusion: Singulair combined with ketotifen in the treatment of patients with AECOPD combined with AHR can significantly improve the efficacy, improve lung function, reduce inflammatory response, and improve the balance of Th17/Treg, effectively controlling the disease.